HAKIKAT DAN POTENSI MANUSIA DALAM IMPLIKASINYA PADA PENDIDIKAN ISLAM (TINJAUAN AL QUR’AN DAN HADITS) - Ulfah, Atiyah; Barni, Mahyuddin; Basir, Abdul; Khairuddin, Ahmad (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2024)
Human nature and its potential is one of the important themes in Islamic education. This theme discusses who humans really are and what potential they have. In the perspective of the Qur'an and hadith, humans are noble creatures and have extraordinary potential. These potentials include the mind, heart and soul. The intellect is the human potential to think and understand. The heart is the human potential to feel and live. The soul is the human potential for action and will. These three potentials must be developed optimally so that humans can achieve the perfection of their lives. An understanding of human nature and its potential is very important for Islamic educators. This understanding will help educators to understand the needs and characteristics of students. Thus, educators can provide education that is appropriate and in accordance with the potential of students.